Innovation from the Himalayas: Natural farming paves the way for sustainable apple production - Sharma, Usha; Gautam, Swati; Sharma, Upinder; Chandel, Rajeshwar Singh (Indian Horticulture, 2026)
Apple cultivation in Himachal Pradesh faces declining productivity, rising input costs, and soil degradation due to prolonged chemical-based farming. Subhash Palekar Natural Farming (SPNF) has emerged as a sustainable alternative emphasizing soil health, biodiversity, and ecological balance. Trials conducted at RHR&TS Mashobra during 2020–24 evaluated SPNF in apple orchards underdifferent rootstock–variety combinations. The results indicated improved soil microbial activity, higher earthworm population, enhanced organic carbon, and better plant growth. SPNF practices, including Jeevamrit, Ghanjeevamrit, mulching, intercropping, and natural pest management, contributed to superior fruit quality attributes such as firmness and ascorbic acid content. Economically,SPNF recorded higher net returns (₹12,74,640/ha) compared to conventional farming (₹8,30,840/ha), demonstrating its potential as a viable, eco-friendly, and profitable approach for sustainable apple production in Himalayan regions.